Impact of circuit rhythms disturbances on the clinical picture of the disease in patients with metabolic syndrome - I. A. Gribanov; E. G. Zarubina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
The purpose of this study was to evaluatey the effect of dark deprivation of various durations on the course of the metabolic syndrome (MS).Material and research methods. To achieve this aim, based on WHO criteria, we selected patients with MS and disturbed circadian rhythms – a total of 102 people (all men) from among people who constantly work at night, in whom a decrease in melatonin levels was recorded at a preliminary stage. In accordance with the tasks set, 102 patients (all men) of working age (young age according to WHO criteria) were divided into three groups of 33, 37 and 32 people, respectively, according to the criterion "duration of work at night and duration of history of MS": 0–5, 5–10 and over 10 years. In the first group, the mean age was 30.1 ± 1.4 years; in the second group, the mean age was 36.5 ± 1.5 years; in the third group, the mean age did not exceed 40.3 ± 0.9 years. As a control group, 45 patients with MS were examined, comparable with the main groups in terms of background pathology and age and different duration of MS history.Results. It was found that the main symptom of MS - abdominal type of obesity (waist circumference more than 80 cm for men) was detected in 100% of patients of the main and control groups of observation. At the same time, it was found that the severity of abdominal obesity is combined with an increase in body mass index (BMI) and tends to increase in patients in the main groups, compared with patients from the control group. In the control group, 35.5% of the examined patients had grade 1-2 hypertension, and another 15.6% had elevated normal blood pressure.Conclusions: In patients with MS, against the background of violations of regulatory mechanisms, the disease is more severe than in patients with a similar history of MS, but without violations of circadian rhythms. The severity of the course of MS against the background of a decrease in the level of melatonin increases with the duration of the violation of regulatory mechanisms.